Tumor Necrosis Factor Family Member Profile Predicts Prognosis and Adjuvant Chemotherapy Benefit for Patients With Small-Cell Lung Cancer - Zhang, Zhihui; Wu, Peng; Zhang, Chaoqi; Luo, Yuejun; Zhang, Guochao; Zeng, Qingpeng; Wang, Lide; Yang, Zhaoyang; Sun, Nan; He, Jie (Frontiers in Immunology, 2021)
Tumor necrosis factor (TNF) family members help to determine the body’s antitumor immunity response and contribute to tumor prognosis and treatment response. However, noting is known about these members in small cell lung cancer (SCLC). Therefore, we conducted this first and most comprehensive investigation of TNF family members in patients with SCLC regarding their possibility to predict prognosis and chemotherapy benefit. Abnormal genetic alterations and expression of TNF family members were found widespread in SCLCs. Then using a LASSO Cox regression model, we built a TNF family-based signature. The signature significantly separated SCLC patients into high- and low- risk groups with distinct survival and chemotherapy benefit in training set (n=77), and was well-validated in the validation sets (n=137) by RT-qPCR. Importantly, the signature exhibited superior predictive performance and identified as a novel independent prognostic factor. Additionally, different immune phenotypes were found between the two groups and high-risk patients had higher CMTM6 expression, which suggesting the potential therapeutic implication for SCLCs at high-risk. We constructed the first clinically applicable TNF family-based signature for predicting prognosis and evaluating benefits from chemotherapy among patients with SCLC. Our findings highlight the ability to predict prognosis and optimize the clinical management of patients with SCLC.